Implementasi akuntansi salam dalam aplikasi shopee - Wardiana, Taufiq Akbar; Nurhayati, Nunung; Ihwanudin, Nandang (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Since the Covid-19 case became a pandemic and there was an appeal not to leave the house, the economic cycle was hampered. Marketplace is here to be a solution so that buying and selling can still occur with minimum contact. The Shopee application is one of the marketplaces known for its many promotions. This study aims to review the implementation of salam accounting in marketplaces in Indonesia, one of which is the Shopee application. The study used qualitative methods with descriptive analysis based on literature review. The results of the study show that the Shopee application has implemented a salam contract in its transactions, where the buyer transacts by paying the full value of the goods, then the goods are sent to the buyer's address, and after the buyer agrees with the condition of the goods, the seller gets the money.